The Impact of Exercise Play on the Biomechanical Characteristics of Single-Leg Jumping in 5- to 6-Year-Old Preschool Children - Zhanbing Song; Bojie Hou; Zhongqiu Ji; Guiping Jiang (Sensors)
Objective: This study aimed to investigate the effects of a 12-week self-designed exercise game intervention on the kinematic and kinetic data of the supporting leg in preschool children during the single-leg jump. Methods: Thirty 5- to 6-year-old preschool children were randomly divided into an experimental group (EG) and a control group (CG). The BTS SMART DX motion capture analysis system was used to collect single-leg jump data before the intervention. The experimental group underwent a 12-week intervention, with self-designed exercise games conducted three times a week for 30 min each session, while the control group only participated in regular kindergarten recess activities and physical education classes. After the intervention, the same equipment was used to collect single-leg jump data again, and the kinematic and kinetic data were analyzed using Anybody 7.4 simulation software. Results: After the intervention, the experimental group showed significant changes in joint angles and joint torques, with a notable increase in the force exerted by dominant muscles such as the vastus medialis, vastus lateralis, and gastrocnemius and a significant increase in the ground reaction force. Although the control group also showed some changes in the dominant muscles, the changes were not as significant as those in the experimental group. Conclusions: A 12-week exercise game intervention significantly improved the technique and force characteristics of 5- to 6-year-old preschool children during the single-leg jump, making muscle exertion more focused and efficient and effectively enhancing explosive power and performance during the single-leg jump.